Uterine Necrosis after Uterine Artery Embolization for Symptomatic Fibroids - Steve Kyende Mutiso; Felix Mwembi Oindi; Nigel Hacking; Timona Obura (Case Reports in Obstetrics and Gynecology)
Introduction. Uterine artery embolization (UAE) is a minimally invasive intervention that is used in the treatment of fibroids. UAE can lead to complications including postembolization syndrome, postprocedure pain, infection, endometrial atrophy leading to secondary amenorrhea, and uterine necrosis. Uterine necrosis after UAE is very rare and hence poses a clinical dilemma for any clinician in its identification and management. We document a case of uterine necrosis after UAE and conduct a literature review on its causation, clinical features, and management principles. Case. A patient presented one month after UAE with abdominal pain and abdominal vaginal discharge. Her work-up revealed features of possible uterine necrosis with sepsis and she was scheduled for a laparotomy and a subtotal hysterectomy was performed. She was subsequently managed with broad spectrum antibiotic and recovered well. Conclusion. Uterine necrosis after UAE is a rare occurrence and we hope the documentation of this case will add to the body of knowledge around it. Theories that explain its occurrence include the use of small particles at embolization, the use of Contour-SE a spherical poly-vinyl alcohol, and lack of collateral supply to the uterus. Its symptoms may be nonspecific but unremitting abdominal pain is invariably present. Finally although conservative management may be successful at times, surgical management with hysterectomy will be required in some cases. The prognosis is good after diagnosis and surgical management.